Social Pathology of Jakarta Society in Brian Khrisna's Novel Sisi Tergelap Surga - Sri Wahyunita Latonga; Asna Ntelu; Herman Didipu (Raja Zulkarnain Education Foundation, 2026)
Social pathology is behavior that does not conform to social norms and can be detrimental to both individuals and society. This study examines the portrayal of the metropolitan lifestyle, forms of social pathology, causal factors, and impacts in Brian Khrisna's novel